Kontingentnost in naključnost kot ruševini časa - Elsaesser, Thomas (Primerjalna književnost, 2014)
The Rings of Saturn by W. G. Sebald is difficult to locate within literary genres (fiction, biography, travel-writing), but is even more disorienting at the intersection of photography, text and images in motion. The essay shows how coincidence, chance and other tropes of contingency are ways of understanding Sebald's strategic use of images, whose enigmatic plurality of meaning makes them the nodal points of intricately networked relationships in space and time.
Keywords: Sebald, W. G., 1944-2001; "Saturnovi prstani"; književnost in film; filmi; German-language literature; nemška književnost; literarni žanri; biografije; spomini